ANALISIS PROBLEMATIKA SISTEM ZONASI PADA KEEFEKTIFAN PROSES PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 2 MALANG - Siti Khodijah; Rosichin Mansur; Moh Eko Nasrullah (VICRATINA, 2020)
Education is the most important thing for the growth and progress of the nation. So as to improve the quality and progress of the Indonesian nation, the government improved its education system by providing a new policy with the zoning system in the PPDB (New Student Reception) process in public and private schools in Indonesia. This zoning system policy has been applied by SMA Negeri 2 Malang, but the implementation of the zoning system at SMA Negeri 2 Malang has many problems, one of which is the decrease in the level of student's willingness to learn especially in Islamic Religious Education subjects. The method used in this study uses a qualitative research approach and type of case study research. Data collection techniques using the method of observation, interviews and documentation. The learning process of Islamic Education after the implementation of the zoning system in SMA Negeri 2 Malang is considered to be less effective, this is due to a decrease in the level of student learning willingness due to the environment and families of low-economic students and lack of attention to education, including in matters of religious learning. Strategies undertaken by Islamic Religious Education teachers to overcome these problems include improving school facilities to support student learning facilities, and using strategies that have been suggested by the government for the learning process of Islamic Religious Education.